Designing ANFIS Controller for MPPT on Photovoltaic System - Wahyu Setyo Pambudi; Riza Agung Firmansyah; Yuliyanto Agung Prabowo; Titiek Suheta; Fathammubina Fathammubina (Universitas Syiah Kuala, 2023)
Photovoltaics’ current and voltage output characteristics depend on the intensity of solar radiation and temperature. Maximum Power Point works with maximum energy output and has the highest efficiency. The maximum energy point tracking method (MPPT) keeps the solar cell operating point at its maximum point. This study uses the Adaptive Neuro-Fuzzy Inference System (ANFIS) method designed and used to maintain that point. The Perturb and Observe (PnO) method is used to test the results, often used in determining this tracking. Based on the test, it was found that the average power efficiency obtained was 84.79%, and using PnO was 83.87%. The transient response using ANFIS is relatively smoother than that of using PnO, which will cause chattering when there is a change in radiation and temperature.